Relative water economy is a useful index of aridity tolerance for Australian poephiline finches - Withers, Philip; Cooper, Christine; Larcombe, Alexander (2022)
We evaluate if the iconic Australian Zebra Finch (Taeniopygia guttata) has a unique physiology or if its metabolic, thermal and hygric physiology are similar to other Australian poephiline finches, by comparing it with three other species, the arid-habitat Painted Finch (Emblema pictum) and the mesic-habitat Double-barred (Taeniopygia bichenovii) and Red-browed (Neochmia temporalis) Finches. All physiological variables responded to ambient temperature as expected. There were no species differences for any of the standard physiological variables, consistent with the hypotheses that birds are pre-adapted to arid habitats, the recent development of Australian deserts has limited opportunity for physiological adaptation, and all four species share similar behavioural and ecological traits. Nevertheless, the ambient temperature where metabolic water production equals evaporative water loss (point of relative water economy) was highest for the Zebra (19.1 °C), lower for Double-barred (16.4 °C) and Painted (15.2 °C) and lowest for Red-Browed (4.1 °C) Finches, corresponding with their general patterns of habitat aridity. The point of relative water economy may be a sensitive index for assessing a species’ tolerance of aridity because it integrates individual physiological variables. We conclude that the Zebra Finch is not a physiological outlier amongst Australian finches, but is at the end of a continuum of aridity tolerance for the four study species.